Supreme Court to prosecute Attorney General for disclosing confidential information - Fernández-Pontes, Inés (Euractiv, 2025)
Supreme Court probe finds evidence Spain’s top prosecutor leaked confidential data in a politically sensitive case tied to Madrid’s regional government.